Molecular Characterization of Helicobacter pylori VacA Induction of IL-8 in U937 Cells Reveals a Prominent Role for p38MAPK in Activating Transcription Factor-2, cAMP Response Element Binding Protein, and NF-κB Activation - Hisatsune, Junzo (2008)
Helicobacter pylori VacA induces multiple effects on susceptible cells, including vacuolation, mitochondrial damage, inhibition of cell growth, and enhanced cyclooxygenase-2 expression. To assess the ability of H. pylori to modulate the production of inflammatory mediators, we examined the mechanisms by which VacA enhanced IL-8 production by promonocytic U937 cells, which demonstrated the greatest VacA-induced IL-8 release of the cells tested. Inhibitors of p38 MAPK (SB203580), ERK1/2 (PD98059), IκBα ((E)-3-(4-methylphenylsulfonyl)-2-propenenitrile), Ca(2+) entry (SKF96365), and intracellular Ca(2+) channels (dantrolene) blocked VacA-induced IL-8 production. Furthermore, an intracellular Ca(2+) chelator (BAPTA-AM), which inhibited VacA-activated p38 MAPK, caused a dose-dependent reduction in VacA-induced IL-8 secretion by U937 cells, implying a role for intracellular Ca(2+) in mediating activation of MAPK and the canonical NF-κB pathway. VacA stimulated translocation of NF-κBp65 to the nucleus, consistent with enhancement of IL-8 expression by activation of the NF-κB pathway. In addition, small interfering RNA of activating transcription factor (ATF)-2 or CREB, which is a p38MAPK substrate and binds to the AP-1 site of the IL-8 promoter, inhibited VacA-induced IL-8 production. VacA activated an IL-8 promoter containing an NF-IL-6 site, but not a mutated AP-1 or NF-κB site, suggesting direct involvement of the ATF-2/CREB binding region or NF-κB-binding regions in VacA-induced IL-8 promoter activation. Thus, in U937 cells, VacA directly increases IL-8 production by activation of the p38 MAPK via intracellular Ca(2+) release, leading to activation of the transcription factors, ATF-2, CREB, and NF-κB.